Experimenting with Financial Professionals - Christoph Huber; Christian König-Kersting (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Financial professionals play a key role in financial markets and the financial industry as a whole. Researchers in experimental economics and finance have therefore started to employ financial professionals as experimental participants. We examine this recent development in the field by reviewing 40 studies from the time period 1986-2022 which compare experimental results from samples of professionals in the finance industry to those from other samples. The considered studies cover a wide array of issues relating to the finance industry, such as risk and uncertainty, asset markets, and financial forecasting, among others. With this comprehensive review, we contribute to recent discussions about external validity and generalizability, aim to synthesize the relevant experimental results, and discuss the key methodological considerations in experimenting with financial professionals.
Keywords: B40; B41; C83; C90; C93; G41; 330; experimental finance; experimental methodology; external validity; generalizability; finance industry